A changing world, a changing role in teaching - Túri, Krisztina (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In the globalized world of the 21st century overwhelmed by Big Data and AI what paradigm shift is needed to be able to create an environment bringing motivation, autonomy and positive pedagogy in the classroom? In this essay some of the most prominant leading models are outlined such as Carl Roger’s and John Heron’s Theory of Facilitation, the Hersey-Blanchard Situational Leadership Theory and that of Bass and Avilio Leadership Styles. Among many others the five predominant disciplines of the learning organization are presented along with the Self-Determination Theory and Attachment Theory. The essay summarizes all those attributes common in these theories, which might be of help to meet the expectations and challenges of this fast-paced, ever-changing world.